2020
DOI: 10.1371/journal.pone.0238986
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reproductive biology of the Greenland shark (Somniosus microcephalus)

Abstract: The Greenland shark (Somniosus microcephalus, Squaliformes: Somniosidae) is a longlived Arctic top predator, which in combination with the high historical and modern fishing pressures, has made it subject to increased scientific focus in recent years. Key aspects of reproduction are not well known as exemplified by sparse and contradictory information e.g. on birth size and number of pups per pregnancy. This study represents the first comprehensive work on Greenland shark reproductive biology based on data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Previous studies have suggested that A. squalicola stunts the gonadal development of some Etmopterid hosts by extracting metabolic resources from their tissues (Eliassen, 2016;Hickling, 1963;Yano & Musick, 2000). Given the much larger body size of Greenland sharks (total length of mature females >400 cm, Nielsen et al, 2020) relative to previously studied host species, it is possible that this effect would be reduced. Nonetheless, further research into the specific mechanism by which A. squalicola affects reproductive development in sharks, and if this is transferable to large-bodied species, is…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have suggested that A. squalicola stunts the gonadal development of some Etmopterid hosts by extracting metabolic resources from their tissues (Eliassen, 2016;Hickling, 1963;Yano & Musick, 2000). Given the much larger body size of Greenland sharks (total length of mature females >400 cm, Nielsen et al, 2020) relative to previously studied host species, it is possible that this effect would be reduced. Nonetheless, further research into the specific mechanism by which A. squalicola affects reproductive development in sharks, and if this is transferable to large-bodied species, is…”
Section: Resultsmentioning
confidence: 97%
“…As for the adult S. microcephalus reported here, these were part of a previous study (Nielsen et al, 2020), with the testicular tissues sourced from specimens captured off Greenland as follows: (A) freshly harvested testes from two specimens that were unintended bycatch during the annual fish surveys of the Greenland Institute of Natural Resources and followed all national laws and regulations of the Government of Greenland, and (B) a donated archival collection of histology preparations from 13 specimens (from 1959 to 1961) captured from commercial seal boats by the late professor emeritus Bjørn Berland (Norwegian Fisheries Research Institute). This valuable archival material includes paraffin blocks and a set of 50 histology slides of a range of dissected tissues, including testicular fragments fixed in either 70% alcohol, formol or Bouin's fixative.…”
Section: Animalsmentioning
confidence: 92%
“…It is important to note, however, that we lack knowledge as to what extent Greenland sharks are able to store energy in their tissues or as undigested food in their stomachs. Furthermore, our estimated energy requirements for this species do not take into account energy investment in growth or reproduction, both of which could increase the energy requirements presented here (Barnett et al, 2017;Nielsen et al, 2020). However, available data in the literature for Greenland sharks suggest a very slow growth rate (∼0.5 cm per year, estimated from a recaptured individual that grew from 262 to 270 cm over a 16 year period; Hansen, 1963), while sharks inhabiting Scott Inlet and Tremblay Sound are mostly sexually immature and consequently should not incur high reproductive costs (Nielsen et al, 2020).…”
Section: Prey Consumption Ratementioning
confidence: 99%
“…Greenland sharks also make up a large proportion of the bycatch in growing commercial fisheries for Greenland halibut (Davis et al, 2013;DFO, 2013). While the population size of Greenland sharks is unknown across most of the Arctic, localized estimates indicate Greenland sharks can be regionally abundant despite their large size and slow sexual maturation (Devine et al, 2018;Nielsen et al, 2020), perhaps in part as a consequence of the low energy requirements, resulting in high carrying capacities for these areas (Brown et al, 2004). Understanding their consumer role in Arctic ecosystems is therefore essential to the proper management of fisheries and to maintaining healthy shark populations in the future (Edwards et al, 2019;Tyrrell et al, 2011).…”
Section: Prey Consumption Ratementioning
confidence: 99%